Complex cardiac surgery in a high-risk patient with new-onset severe mitral regurgitation and aorta to right ventricular fistula after transcatheter aortic valve implantation: a case report. Issue 5 (2nd October 2020) - Verdugo-Marchese, Mario; Monney, Pierre; Muller, Olivier; Kirsch, Matthias
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is the procedure of choice for aortic stenosis in high surgical risk patients, but it is no free from complications. Case summary: A 86-year-old patient with severe aortic stenosis underwent TAVI 3 years ago with an Edwards Sapiens valve by femoral access. In the echocardiography follow-up, an aorta–right ventricular (Ao-RV) fistula was noted with restrictive flow and no significant shunt and it was treated conservatively. Three years after TAVI, the patient underwent cardiac surgery because of worsening heart failure due to a severe degenerative mitral regurgitation with tethering of P2 due to left ventricular remodelling, a posterior jet of severe regurgitation, and left ventricular dilatation. Surgical replacement of the TAVI and aortic root with a bioprosthesis (Medtronic Freestyle) and direct closure of the fistula was performed along with the mitral valve replacement. The patient was discharged with a good clinical result and no evidence of remaining Ao-RV fistula at transthoracic echocardiography. Discussion: Aorta–right ventricular fistula is a rare entity. Most reported cases arise after rupture of a congenital coronary sinus aneurism, endocarditis, trauma, and aortic valve or aortic root surgery. This is the 10th reported case after TAVI (9 after an Edwards Sapiens TAVI). Non-significant shunt can be treated conservatively but development of heart failure and death are described in significant shunts. Balloon post-dilatation and the absence of surgical calcium debridement inherent to TAVI may theoretically contribute to the development of the fistula. Surgical replacement and closure of the fistula is a therapeutic option for this entity even in high-risk patients.